TGFBR1 gene silencing attenuates cardiomyopathy in the HFpEF mouse model - Xuanyang Shen; Weidong Li; Xiaolu Jiang; Hongfu Wen; Yuan Shen; Wen Zhang; Yongjian Peng; Guoping Kang (PLoS ONE, 2025)
Myocardial fibrosis is a principal factor in the progression of heart failure with preserved ejection fraction (HFpEF). Prior research has substantiated the profibrotic impact of transforming growth factor β1. Nevertheless, the function of the transforming growth factor beta receptor (TGFBR) in HFpEF remains uncertain. In this study, we found an increase in myocardial TGFBR1 expression in mice with HFpEF. Silencing of the TGFBR1 gene improved cardiac function in HFpEF mice by attenuating cardiac fibrosis, reducing myocardial hypertrophy, and ameliorating myocardial remodeling. At the mechanistic level, TGFBR1 gene silencing led to a reduction in myocardial collagen synthesis through the Smad2/3 signaling pathway and an inhibition of cardiac hypertrophy through the mitogen-activated protein kinase (MAPK) signaling pathway in HFpEF mice. Additionally, we discovered that TGFBR1 gene silencing mitigated myocardial remodeling in HFpEF mice by suppressing TAK1-mediated PANoptosis, primarily because TGFBR1 gene silencing impeded the dissociation of RIPK1 and TAK1 and reduced Tumor Necrosis Factor Receptor-Associated Factor 6 expression. These findings indicate that TGFBR1 gene silencing enhances cardiac remodeling and function and represents a potential therapeutic target for the treatment of HFpEF.